2018
DOI: 10.1002/adom.201800198
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Molecular Packing on the Emissive Behavior of Pyrene Derivatives: Mechanoluminescence and Mechanochromism

Abstract: Although some bright, organic mechanoluminescence (ML) luminogens with aggregation‐induced emission properties and twisted molecular structures are recently reported, those with planar structures and bright ML and their related effective design strategies are not yet explored, partially due to aggregation‐caused quenching in luminogens with planar structures. Herein, using the unique solid‐state packing style of pyrene, bright dual monomer‐excimer‐ML and excimer‐ML from two pyrene derivatives (Py‐Bpin and Py‐B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 70 publications
1
87
0
Order By: Relevance
“…This could effectively restrict non-radiative transitions by decreasing the molecular slippage under the mechanical stimulation, then contribute much to the ML effect. [7,8,10] Only after being ground heavily,c ould it transform to the nearly amorphous state without obvious peaks.I nc onsideration of the two remained emissive peaks after heavy grinding,t he mechanochromism effect of FCO-CzS could not be simply ascribed to the transition of packing mode,such as crystal to amorphous state.I tw as considered that the changes of molecular conformation from quasi-axial to quasi-equatorial one of phenothiazine group under mechanical stimulus might have played the key role.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…This could effectively restrict non-radiative transitions by decreasing the molecular slippage under the mechanical stimulation, then contribute much to the ML effect. [7,8,10] Only after being ground heavily,c ould it transform to the nearly amorphous state without obvious peaks.I nc onsideration of the two remained emissive peaks after heavy grinding,t he mechanochromism effect of FCO-CzS could not be simply ascribed to the transition of packing mode,such as crystal to amorphous state.I tw as considered that the changes of molecular conformation from quasi-axial to quasi-equatorial one of phenothiazine group under mechanical stimulus might have played the key role.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Accordingly,b ased on our experience on ML luminogens,p heno- thiazine (electron donor) and 4-fluorobenzophenone (electron acceptor) groups were integrated together to yield FCO-CzS,i nw hich, the D-A structure could further reinforce the dynamic electronic character and related emissive property in response to the dynamic molecular conformation, while the fluorine atom could enhance the intermolecular interactions and restrict the nonradiative transition, thus to promote the emission, both for PL and ML. [7,8,10] Excitedly FCO-CzS exhibited changeable mechanoluminescence from blue to white and yellow under continuous mechanical stimulus.T othe best of our knowledge,this is the first example of dynamic mechanoluminescent luminogens. Careful analyses of experimental results,c oupled with wellunderstood PL theory,showed that the molecular conformation transition from quasi-axial to quasi-equatorial should be responsible for the interesting dynamic ML effect.…”
mentioning
confidence: 99%
“…[9a] This told us that the conformation of phenothiazine derivatives could be changed upon the mechanical stimuli. [7,8,10] Excitedly FCO-CzS exhibited changeable mechanoluminescence from blue to white and yellow under continuous mechanical stimulus.T othe best of our knowledge,this is the first example of dynamic mechanoluminescent luminogens. Accordingly,b ased on our experience on ML luminogens,p heno- thiazine (electron donor) and 4-fluorobenzophenone (electron acceptor) groups were integrated together to yield FCO-CzS,i nw hich, the D-A structure could further reinforce the dynamic electronic character and related emissive property in response to the dynamic molecular conformation, while the fluorine atom could enhance the intermolecular interactions and restrict the nonradiative transition, thus to promote the emission, both for PL and ML.…”
mentioning
confidence: 99%
“…The molecular packing should play ak ey role in these stimuli-responsive chromatic properties because this packing dictates the energy gaps between the HOMO and LUMO of excimers, as shownb yother researchers. [15] Further investigationw ith the aid of theoretical calculations is in progress in understand the precise reason for the differentemission properties in amorphous and crystalline phases.…”
Section: Characteristics Of the Condensed States:m Echano-thermo- Anmentioning
confidence: 99%